2022
DOI: 10.1186/s13054-022-03915-3
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Critical Care Medicine

Abstract: This article is one of ten reviews selected from the Annual Update in Intensive Care and Emergency Medicine 2022. Other selected articles can be found online at https://www.biomedcentral.com/collections/annualupdate2022 . Further information about the Annual Update in Intensive Care and Emergency Medicine is available from https://link.springer.com/bookseries/8901 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 48 publications
(49 reference statements)
0
61
0
1
Order By: Relevance
“…This study did not focus on predicting adverse outcomes, but instead focused on prompt interventions, which can support major clinical decisions and potentially improve patients’ outcomes. Recent review in literatures demonstrated that major predictors for AI are patient's conditions as recognizing clinical conditions, predicting disease evolution, or predicting outcome 26 28 . In recent years, several AI-related studies have concentrated on clinical decision-making, action-based learning, such as using reinforcement learning 26 , 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study did not focus on predicting adverse outcomes, but instead focused on prompt interventions, which can support major clinical decisions and potentially improve patients’ outcomes. Recent review in literatures demonstrated that major predictors for AI are patient's conditions as recognizing clinical conditions, predicting disease evolution, or predicting outcome 26 28 . In recent years, several AI-related studies have concentrated on clinical decision-making, action-based learning, such as using reinforcement learning 26 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent review in literatures demonstrated that major predictors for AI are patient's conditions as recognizing clinical conditions, predicting disease evolution, or predicting outcome 26 28 . In recent years, several AI-related studies have concentrated on clinical decision-making, action-based learning, such as using reinforcement learning 26 , 29 . This study suggests actions, not only decisions, in which it is distinct from those of earlier research 30 33 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several untapped areas and much needed to be explored fields in critical care such as research in extracorporeal life support, telemedicine and artificial intelligence algorithms which involve multicentre data sharing and applicability in real time. [ 19 ] The coronavirus disease 2019 pandemic has brought in huge opportunities along with unforeseen challenges for researchers in the critical care unit as evidenced by the continuing shower of research publications. [ 20 - 25 ]…”
Section: Improving the Quality Of Research In The Icu Patientmentioning
confidence: 99%
“…Given this dynamic and data-rich environment, the ICU is pre-eminently a place where artificial intelligence (AI) holds the promise to aid clinical decision making. [1][2][3] So far, however, most AI models developed for the ICU remain within the prototyping phase. 4,5 One explanation for this may be that most models in the ICU are built for the task of prediction, ie, mapping input data to (future) patient outcomes.…”
Section: Introductionmentioning
confidence: 99%